Pengaruh Online Marketing Dan Biaya Ongkos Kirim Terhadap Keputusan Pembelian Pada UMKM Pisang Pasir Memey - Reni Yusnita; Annio Indah Lestari Nasution; Nursantri Yanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Banana Pasir Memey is a business in Saentis Village that uses Facebook and WhatsApp as sales objects. The Banana Pasir Memey Facebook account has 4,982 followers and each post always has an increase in total likes every year as well as total comments. The positive impact for the UMKM of the Pasir Memey bananas is experiencing an increase in sales in 2020-2022, the negative impact for the UMKM of the Pasir Memey bananas is the shipping costs charged to buyers which will later be taken into consideration when making purchasing decisions. The aim of the research is to test and analyze the influence of online marketing and shipping costs on purchasing decisions among the Pasir Memey Banana UMKM in Saentis Village. This type of research uses a descriptive quantitative approach carried out on customers who have purchased Banana Pasir Memey products, using questionnaire data with a total sample of 70 respondents. The sampling technique is through random sampling technique. The analytical methods used are validity test, reliability test, classical assumption test, multiple linear regression test, t test, and f test. The results of the research show that online marketing has no significant influence on purchasing decisions and shipping costs have a significant influence on purchasing decisions for UMKM customers of Pasir Memey bananas. The simultaneous test shows that the online marketing variables and shipping costs simultaneously have a positive and significant effect on purchasing decisions.